Senif zakat for muallaf in aceh (Overview of Politics, Economics and Psychology of Religion) - Muhammad Syarif Syarif (Journal of Law Science, 2023)
It is interesting to study the art of Muallaf in the asnaf of zakat as contained in the letter at-Taubah verse 60, considering that the current condition of Islam is different from the condition at the time of Rasulullah SAW. the current condition of Islam in Aceh is very strong, besidesculture Aceh, which is very thick with Islamic culture, is then supported by legitimacy in the law to carry out Islamic law in a kaffah manner. Therefore, for the existence of converts in Aceh, presumably the practice of the caliph Umar bin khattab above can be implemented properly and needs to be reinterpreted in the meaning of converts according to the conditions of Aceh today. This type of research is descriptive research using a qualitative approach, using literature research methods (literature review) and using narrative analysis writing using descriptive data. Research results show thatConverts are those whose faith is still weak so that they are worried that they will feel uncomfortable in Islam, but if they are given zakat they will certainly be happy. They can also come from Muslim and non-Muslim leaders, they can be rebels who are worried about fighting Muslims, whether they need financial help from Muslims or not. But they can be given zakat based on the assessment of Islamic leaders or the person giving zakat himself. The right to convert still exists, it just depends on each region and its leaders from all ages. Therefore, if there is a reason to tame the hearts of the asnaf Muallaf Qulubuhum, that is to strengthen and defend Islam, then this group can be given zakat as it was done by the Prophet. Baitul Mal Aceh Aceh seems to prioritize productive practices rather than consumptive zakat given to converts. this can be seen from the zakat distribution activities of the muallaf art, namely Business Capital Assistance and Student Fees for the children of the muallaf